2008
DOI: 10.1126/science.1150421
|View full text |Cite
|
Sign up to set email alerts
|

Designed Protein-Protein Association

Abstract: The analysis of natural contact interfaces between protein subunits and between proteins has disclosed some general rules governing their association. We have applied these rules to produce a number of novel assemblies, demonstrating that a given protein can be engineered to form contacts at various points of its surface. Symmetry plays an important role because it defines the multiplicity of a designed contact and therefore the number of required mutations. Some of the proteins needed only a single side-chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
137
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(141 citation statements)
references
References 26 publications
3
137
0
1
Order By: Relevance
“…The ring-shaped dimer has a contact area of ϳ1860 Å 2 . This number significantly exceeds the threshold value of 600 Å 2 above which physiologically relevant dimers are to be expected (54). The other putative dimers in the crystal packing (Table 2) have significantly lower contact areas, not exceeding 659 Å 2 .…”
Section: Resultsmentioning
confidence: 90%
“…The ring-shaped dimer has a contact area of ϳ1860 Å 2 . This number significantly exceeds the threshold value of 600 Å 2 above which physiologically relevant dimers are to be expected (54). The other putative dimers in the crystal packing (Table 2) have significantly lower contact areas, not exceeding 659 Å 2 .…”
Section: Resultsmentioning
confidence: 90%
“…The large residue (Tyr1) at the N terminus of P6-a may also contribute to destabilization of the parallel configuration. Charged side-chains often have high conformational entropy, and they are believed to disrupt crystal-packing interfaces (8,52,53,57,58). These residues are frequently mutated to induce crystallographic order (54,59).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous paper we demonstrated that specific function and binding selectivity in homodimers might be also sustained by disordered loops (52). We should mention, that although here we did not study explicitly the amino acid substitutions which can govern the complex formation, previous studies clearly showed that most of these substitutions involved aromatic and hydrophobic residues which increased binding affinity and stabilized the homooligomer (53,54), but at the same time compromised the specificity and reversibility of the complex formation. Finally, our analysis concludes that presence of enabling and disabling features can be a strong predictor of the oligomeric state once these features are found in the target protein, resulting in the lower false positive rate and high precision of the prediction.…”
Section: Enabling and Disabling Regions Are Important For Developing Newmentioning
confidence: 99%